2023
DOI: 10.1021/acsnano.2c09762
|View full text |Cite
|
Sign up to set email alerts
|

Collective Magnetic Behavior in Vanadium Telluride Induced by Self-Intercalation

Abstract: Self-intercalation of native magnetic atoms within the van der Waals (vdW) gap of layered two-dimensional (2D) materials provides a degree of freedom to manipulate magnetism in low-dimensional systems. Among various vdW magnets, the vanadium telluride is an interesting system to explore the interlayer order−disorder transition of magnetic impurities due to its flexibility in taking nonstoichiometric compositions. In this work, we combine high-resolution scanning transmission electron microscopy (STEM) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…It is noteworthy that these techniques possess multiple capabilities and have wide‐ranging applications, including super‐resolution imaging, [ 140c ] low‐dose imaging, [ 147 ] mapping of strain, [ 148 ] electric, [ 149 ] and magnetic field. [ 27a,150 ] Some of them have been introduced in previous review papers. [ 30,149a,151 ] In this discussion, we will focus specifically on the application of 4D‐STEM and DPC techniques for mapping the local electric and magnetic fields in TMDs, thereby enabling functional imaging of TMDs.…”
Section: Real‐space Imaging Of 2d Tmds At the Atomic‐scalementioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that these techniques possess multiple capabilities and have wide‐ranging applications, including super‐resolution imaging, [ 140c ] low‐dose imaging, [ 147 ] mapping of strain, [ 148 ] electric, [ 149 ] and magnetic field. [ 27a,150 ] Some of them have been introduced in previous review papers. [ 30,149a,151 ] In this discussion, we will focus specifically on the application of 4D‐STEM and DPC techniques for mapping the local electric and magnetic fields in TMDs, thereby enabling functional imaging of TMDs.…”
Section: Real‐space Imaging Of 2d Tmds At the Atomic‐scalementioning
confidence: 99%
“…Guzman et al revealed the formation of diffuse magnetic domain structures in V 1+x Te 2 by 4D-STEM imaging, which originate from the collective magnetism of ensembles of magnetic V 3 Te 4 nanoclusters. [150] Figure 7i illustrates the reconstructed magnetic induction magnitude (left panel) and magnetic field vector (right panel) maps revealing the presence of nanometer-size clusters surrounded by a nonmagnetic background, and the formation of uniformly magnetized domains, respectively. To ensure the reconstructed contrast is intrinsically contributed by the local magnetic field of V x Te y domains, Guzman et al conducted control experiments on a nonmagnetic sample and vacuum.…”
Section: Functional Imaging Beyond Atomic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the contact, electrons are transferred until the work functions are equal. 34,35 Chemical doping, 36 nanostructure engineering, 37 and construction of hybrids 38 are all viable strategies for fulfilling the fabrication of heterostructures. It consequently seems extremely positive to combine alternative construction approaches to create heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…For different concentrations, in-plane ordered 2 × 2, √3 × √3 R30°, or 2 × 1 superstructures are known . Previous studies of ultrathin pseudo 2D crystals of this class are based on known bulk phases or self-intercalation compounds (i.e., only one kind of TM). ,, Bulk-exfoliated sheets or thin films of these materials have demonstrated important phenomena, such as concentration-dependent magnetic anisotropy and skyrmion lattices in Cr 1+δ Te 2 , , magnetic properties of self-intercalated TaS 2 and in VSe 2 and VTe 2 , proposed superconductivity in Ni 1+δ Te 2 , layer-dependent magnetism in CrCuSe 2 , and demonstration of heteroepitaxy of CuCr 2 Te 4 . In contrast to these reports, a novel synthesis approach is discussed here that enables incorporation of various TMs between TMD sheets.…”
mentioning
confidence: 99%